870 Contextualised knowledge synthesis for local stakeholders in ohs. (24th April 2018) - Irvin, Emma; Bornstein, Stephen; Cullen, Kim; Butt, Amanda; Eerd, Dwayne Van; Johnson, Leslie; Passmore, Steven; Saunders, Ron
Abstract : Introduction: Effective decision-making in occupational health and safety (OHS) requires having up-to-date evidence on what works from the best available research. However, the research literature does not typically take into account how implementation may be constrained by the demographic, economic or resource context of a jurisdiction/region that is considering action. Evidence-informed practices and policies need to be made based not only on an understanding of 'what works', but also on an understanding of 'what will work here'. Our objective was to develop and test an innovative methodology for synthesising and contextualising current scientific knowledge in occupational health and safety. Methods: The teams combined methods used by the 'Contextualised Health Research Synthesis Program' (CHRSP) at the Newfoundland and Labrador Centre for Applied Health Research (NLCAHR) with techniques for systematic reviewing and reporting pioneered by the Systematic Review Program at IWH. In our pilot testing we collected data about important contextual factors from key stakeholders through interviews or focus groups. Result: The method we developed describes a variety of synthesis methods that can be used by researchers and stakeholders for evidence-based decision-making. In addition, we describe the process of gathering contextual information from key stakeholders. In one example related to depression in the workplace, we found that contextual factors of geography, industry/workplace, safey culture were important for stakeholders to consider in implementing evidence-based interventions. Discussion: The project resulted in the creation of Evidence in Context Occupational Health and Safety Operational Handbook and an updated systematic review Managing Depression in the Workplace that was contextualised for the province of Manitoba (http://www.iwh.on.ca/systematic-reviews). The methodology has been transferred to end users in three Canadian provinces to date, Newfoundland and Labrador, Ontario and Manitoba. The handbook is a practical and relatively inexpensive way for OHS stakeholders to synthesise and contextualise evidence for decision making.